WHAT IS DEMOCRACY? A MEDIA CONCEPT: (Socio-Cultural Linguistic Analysis) - Mubarak, Muhammed Ridha (ALBAHITH ALALAMI, 2013)
It is easy to talk about democracy, but it is difficult to practice. We talk about postmodernism, but difficult to be embodied in the ground. Yet, the age of democracy and modernity at the same time prompted the researcher to try to find a media concept for it. It does not mean that this concept has not yet formed. But the rooting of democracy and the approaching of states and groups towards it, made it necessary to by studied again. The relationship between democracy and the media has made them look like one concept. The existence of one is linked to the existence of the other. The reality is only a linguistic formulation, but the social and cultural aspect is related to democracy originating and communication. We have studied very briefly the evolution of democracy from its emergence as a philosophy of governance to its roots in human thought in general. The human groups have yet to find a reasonable alternative to democracy. As a clue to that, the cultural structures that accompanied democracy in its long history, and the divergences that have passed through. The unity of the two concepts forced the researcher to plead the linguistic potential, without which we could not understand democracy and the associated practice. Perhaps the media, the space in which democracy moves, has created a practical space for its work